Gluten indeks ve alveograf parametrelerinin Türk ekmek tipi için kullanımı - Büyükcan, Tanzer (Fen Bilimleri Enstitüsü, 1996)
Bu çalışmada çeşitli unların gluten indeks değerleri ve alveograf parametreleri ile bu unlardan yapılan standart ekmeklerin hacim değerleri arasındaki ilişki belirlenmeye çalışılmıştır. Bu amaçla, her coğrafi bölgeden ikişer adet Tip 1 (65'e kadar randımanlı) ve Tip 2 (66-72 randımanlı) olmak üzere 4 ayrı un örneği, tesadüfi olarak seçilmiş un fabrikalarından temin edilmiştir. Bu örneklere temel analizler olarak nem, kül, protein, düşme sayısı (alfa-amilaz enzim aktivitesi) ve yaş gluten tayinleri gerçekleştirildikten sonra gluten indeks ve alveograf denemeleri yapılmıştır. Ekmek yapımında kullanılacak olan su miktarının tespit edilmesi amacıyla farinograf denemesi yapıldıktan sonra, ekmeklerin yapımı tamamlanmış ve ekmek hacimleri belirlenmiştir. Deneysel verilerin elde edilmesinin ardından, gluten indeks ve alveograftan elde edilen değerler ile ekmek hacmi arasındaki ilişkinin belirlenmesi amacıyla basit lineer regresyon analizi yapılıp korelasyon katsayıları hesaplanmıştır. Bulunan korelasyon katsayısı değerlerinden, ekmek hacmi ile istatistiksel olarak önemli ilişki gösteren parametreler; protein miktarı (r=0.7488), alveograf enerji (W) (r=0.6319), uzayabilirlik (L) (r=0.6465) şişme indeksi (G) (r=0.6182), gluten mukavemeti (P) (r=-0.4371) ve konfügurasyon (P\L) (r=-0.5248) olarak belirlenmiştir. Alveograf parametrelerinden gluten mukavemeti (P) ve konfügurasyon (P\L) değerleri ile ekmek hacmi arasında negatif bir ilişki saptanmıştır. Gluten indeks ve ekmek hacmi arasında önemli bir ilişki bulunamamıştır (r=-0. 1 69 1 ). Alveograf parametrelerinin Türk ekmek tipine ait spesifikasyonlan belirlenmiştir. Araştırmada kullanılan un örnekleri için gluten mukavemeti (P) 60-70 arasında, uzayabilirlik (L) 80-90 civarında, şişme indeksi (G) 20'nin üzerinde ve enerji (W) 180'den yüksek olduğunda Türk tipi ekmek için yüksek hacim değerleri elde edilmiştir.

Flour quality is the key factor in producing baked foods. At this time, we are still not clear about moleculer interactions which lead to good flour quality. Bakers and flour millers have developed some indicators that partially describe flour quality. These factors give some indications about the suitability of a flour for making bread. They alone are not sufficient to define flour quality. The baker is also interested in flour strength. Flour strength is also effective on the bread making performance of the flours. Gluten index and alveograph are used to estimate this characteristic. At this time, milling sector is in the competition in order to manufacture flour with higher quality. This would be possible first of all by producing standard and high quality flour. Quality and suitability of a flour for making bread can be predicted by using this instruments in the mills manufacturing flour with modern technology. Bread making performance of a flour is predicted by comparing gluten index and alveograph parameters: Tenacity (P), extensibility (L), deformation energy (W), swelling index (G), and configuration (P?L), with standard values obtained before. Since there is no study on this subject, in our country up to date, values are interpreted by comparing these values with values obtained for pan breads in Europe, and results may be misleading. The flour characterized as good quality in the mill causes to problems during bread making. Bread making performance of flours can not be used completely. In this study, the relationships between gluten index and alveograph parameters, and volumes of standard Turkish type breads were investigated in order to determine bread making performance of flours completely. In order to find out the relationship between gluten index and alveograph parameters, and volumes of Turkish type breads, 4 samples from 7 geographical regions (a total of 28 samples) have been obtained randomly. Two of four samples were Type 1 (up to 65% extraction) and the others were Type 2 (65-72% extraction). First of all, vin moisture, protein, ash, falling number, gluten index and wet gluten values were determined by using the approved methods of the American Association of the Cereal Chemists (AACC). Moisture, ash and falling number values of the flour samples are similar for the regions. Moisture contents of all flour samples are high when compared to average value for our country, 10-14% (Table I). The falling number values are also higher than 250 which is normal value (Table I). Protein contents except East and South Anatolia Regions have ranged between 10-14% level determined for our country conditions (Table I). Table I. Moisture, ash, protein, wet gluten and gluten index values of the flour samples. IX It has been observed that protein and gluten contents have been varied between regions. This may be due to the differences in environmental conditions (climate, soil) and production conditions (fertilization, irrigation, mechanized agriculture) between regions. Since the environmental and production conditions are unsuitable in especially East and South Anatolian regions, protein contents may be determined lower in this regions. After chemical analyses, alveograph test results were obtained (Table II). Table II Alveograph parameter values of the flour samples. Then flour samples were tested on a Brabender Farinograph to determine the amount of water to be added during bread making (AACC method) (Table HI). A conventional straight dough procedure was utilized for baking and resulting loaf volumes in the unit of cubic centime were measured by a seed displacement method (Table HI). Table HI. Water absorption capacity values of dough and bread volumes (cm3). Simple linear regression analysis was applied to data, using statistical Microstat package program, to determine whether bread volume could be predicted by alveograph and gluten index parameters. Simple correlation coefficients were also determined (Table TV). \ XI Table IV. Correlation coefficients between bread volumes and protein, wet gluten, alveograph and gluten index parameters (r values) (n=28). The results showed that five alveograph parameters,the energy (r=0.6319), extensibility (r=0.6465), swelling index (r=0.6182), tenacity (P) (r=-0.4371) and configuration (P\L) (r=-0.5248) in addition to flour protein (r==0.7488), could be used to predict the volumes of Turkish type bread. Also, there is an high correlation between gluten content and bread volume (r=0.9506). No correlation was observed between gluten index value and bread volume (r=- 0.1691). It has been observed that flours with a high gluten index value but low gluten yielded lower bread volume. Gluten index value alone is not sufficient to determine bread volume. Therefore both a certain quantity and quality of gluten is needed in wheat flour to produce a satisfactory quality bread. High correlation was also determined between water absorption capacity and bread volumes (r=0.9155). Specifications of the alveograph parameters of the Turkish bread type were determined. When tenacity (P) value was between 50-60, extensibility (L) was about 80-90, swelling index (G) value was above 20 and energy (W) value was above 180, high loaf volume can be obtained for a Turkish type of bread.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Ekmek; Un; Bread; Flour